Parametric Presburger arithmetic: logic, combinatorics, and quasi-polynomial behavior - Tristram Bogart; John Goodrick; Kevin Woods (Discrete Analysis, 2017)
Parametric Presburger arithmetic: logic, combinatorics, and quasi-polynomial behavior, Discrete Analysis 2017:4, 34 pp.